2012
DOI: 10.1002/fam.2166
|View full text |Cite
|
Sign up to set email alerts
|

Effect of flame heat flux on thermal response and fire properties of char‐forming composite materials

Abstract: SUMMARY This study evaluates the effect of flame heat flux on the prediction of thermal response and fire properties of a char‐forming composite material. A simplified two‐layer flame model was developed and incorporated into a heat transfer thermal model to predict the thermal response and fire reaction characteristics of a burning material. A typical char‐forming material, E‐glass reinforced polyester composite, was used in the study. A cone calorimeter was used to measure the fire reaction characteristics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…The average flame fluxes arriving at the composite were determined as 4.5 and 3.5 kW/m 2 at heat flux levels of 35 and 45 kW/m 2 , respectively . The effective flame heat flux was approximated by Equation .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The average flame fluxes arriving at the composite were determined as 4.5 and 3.5 kW/m 2 at heat flux levels of 35 and 45 kW/m 2 , respectively . The effective flame heat flux was approximated by Equation .…”
Section: Resultsmentioning
confidence: 99%
“…In , the flame effect under different external heating flux for the same FRP composite material in this paper was studied. It was reported that the maximum flame effect was achieved at the very beginning of flaming ignition and then decreased almost linearly and became very small (approaching to zero) at the end (Figure ).…”
Section: Effect Of Combustion Flame On Temperature and Mass Lossmentioning
confidence: 99%
See 2 more Smart Citations
“…[ 40 ] Recent studies specifically have addressed the questions related to the tensile behavior of carbon/polyphenylene sulfide (C/PPS) under very high‐temperature conditions, with an emphasis on the evolution of the mechanical properties along with temperature higher than the onset of thermal decomposition temperature. [ 19,20 ] To better understand the changes in the thermal and mechanical behaviors of TP‐based composites under fire exposure the first step usually is to investigate the influence of temperature resulting from homogeneous [ 30 ] or heterogeneous temperature conditions. [ 31,32 ]…”
Section: Introductionmentioning
confidence: 99%